Performance of Piper Nigrum (Black Pepper) as Corrosion Inhibitor of Ductile Iron - Faizul Idham, Mohd; Fathmi Masor, Mohamad; Mohd, Norzila; Abdullah, Bulan; Khadijah Alias, Siti (International Journal of Engineering and Technology, 2018)
The effectiveness of Piper Nigrum as green corrosion inhibitor towards ductile iron in 1M Sodium Hydroxide was studied. Piper Nigrum, also known as black pepper had undergone extraction process in order to get the final product in the form of liquid which acted as inhibitor. The sample of this inhibitor was analyzed by Fourier Transform Infrared Spectroscopy (FTIR) in determining the bonding and the functional group of the inhibitor. Meanwhile, the capability of Piper Nigrum to inhibit corrosion was tested based on concentration of inhibitors by using the gravimetric method. Ductile iron was exposed to 1M Sodium Hydroxide which acted as corrosive medium and inhibitor concentration of 0.1, 0.2 and 0.3 g/L respectively for three hours at constant temperature of 50°C. In addition, there was one ductile iron which was exposed to 1M Sodium Hydroxide in the absence of inhibitor. The ductile iron was then visualized by the microstructure observation through microscope. As a result, FTIR had indicated that the presence of hetero atoms in alkaloids Piperine made Piper Nigrum to have an ability to inhibit corrosion. Besides, Piper Nigrum could achieve maximum inhibition efficiency of 97.97% while the corrosion rate was only 0.8059 mm/year at 0.3 g/L inhibitor. Furthermore, the concentration of inhibitor gave insignificant effect on the microstructure. However, the morphology of ductile iron microstructure had shown slight difference when the ductile iron was immersed in higher concentration of inhibitor. This had proved that the higher concentration of inhibitor, the less corrosion occurred.